2018
DOI: 10.3389/fncel.2018.00328
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Excitability and Increased Neurite Complexity of Cortical Interneurons in a Familial Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Cortical interneurons play a crucial role in regulating inhibitory-excitatory balance in brain circuits, filtering synaptic information and dictating the activity of pyramidal cells through the release of GABA. In the fatal motor neuron (MN) disease, amyotrophic lateral sclerosis (ALS), an imbalance between excitation and inhibition is an early event in the motor cortex, preceding the development of overt clinical symptoms. Patients with both sporadic and familial forms of the disease exhibit reduced cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…The electrical properties of CSMN at this early stage of P30 demonstrated conflicting excitatory and inhibitory factors. Similar to our findings, there are reports to support hyperexcitability (van Zundert et al, 2008;Vucic et al, 2009;Wainger et al, 2014;Fogarty, 2018), but on the other hand also on reduced excitability (Mills, 2003;Delestrée et al, 2014;Leroy et al, 2014;King et al, 2016;Clark et al, 2018). We believe that hyper and/or hypo excitability is a dynamic phenomenon, and it is a function of disease state.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The electrical properties of CSMN at this early stage of P30 demonstrated conflicting excitatory and inhibitory factors. Similar to our findings, there are reports to support hyperexcitability (van Zundert et al, 2008;Vucic et al, 2009;Wainger et al, 2014;Fogarty, 2018), but on the other hand also on reduced excitability (Mills, 2003;Delestrée et al, 2014;Leroy et al, 2014;King et al, 2016;Clark et al, 2018). We believe that hyper and/or hypo excitability is a dynamic phenomenon, and it is a function of disease state.…”
Section: Discussionsupporting
confidence: 92%
“…They are present throughout the motor column and numerous studies tried to reveal potential changes in their numbers concerning disease progression. Even though some results appear to contradict, overall analyses suggest that the distribution and the function of interneurons are an important component of UMN circuitry (Ziemann et al, 1997;Clark et al, 2018). The inhibitory input can be monosynaptic (direct) and disynaptic (via another neuron).…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, found PV interneurons to be unaltered presymptomatically and to turn hyperexcitable during the symptomatic phase in the same SOD1 G93A mouse model 87 . In either case, those changes in PV excitability were always accompanied by hyperexcitability of layer V pyramidal neurons [84][85][86][87] . These findings in mouse models nicely recapitulate human ALS pathology, in which cortical hyperexcitability is a frequent and, most importantly, early finding in familial and sporadic cases, including FUS mutation carriers 16,88 .…”
Section: Discussionmentioning
confidence: 96%
“…Illustrating this, loss of Gabra1 77 , or of Gabra3 78 are sufficient to lead to locomotor hyperactivity and the FUS target Nrxn1, encoding a critical actor in the formation of GABAergic and glutamatergic synapses 79 , is critical in locomotor activity and social behavior in mice 80,81 . Indeed, deletion of all three neurexins from PV neurons is causing a decrease in the number of synapses in this neuronal type 82 [84][85][86] . Others, however, found PV interneurons to be unaltered presymptomatically and to turn hyperexcitable during the symptomatic phase in the same SOD1 G93A mouse model 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models of the disease have further substantiated the notion of compromised inhibition in ALS pathophysiology. Whole-cell patch-clamp recordings of cultured interneurons from embryonic Gad67-GFP:SOD1 G93A mice revealed that interneurons (subtype not specified) were morphologically less complex and less excitable (Clark et al, 2018). Subtype-specific investigations have furthermore unraveled a selective impairment of different interneuron populations.…”
Section: Compromised Inhibitionmentioning
confidence: 99%